2016
DOI: 10.1097/rli.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Screening With Computed Tomography Using the Arterial Enhancement Fraction With Radiologic-Pathologic Correlation

Abstract: Objective: The aim of this study was to investigate the performance of the arterial enhancement fraction (AEF) in multiphasic computed tomography (CT) acquisitions to detect hepatocellular carcinoma (HCC) in liver transplant recipients in correlation with the pathologic analysis of the corresponding liver explants. Materials and Methods: Fifty-five transplant recipients were analyzed: 35 patients with 108 histologically proven HCC lesions and 20 patients with end-stage liver disease without HCC. Six radiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Increased angiogenesis is accompanied by an increased distribution of contrast agents in the intravascular/extravascular compartment (8), thereby resulting in a higher AEF value during the same circulatory phase. Additionally, unlike NIC and λ HU , the AEF can distinguish the relationship between different phases of the same blood circulation (26). Secondly, the spectral detector CT used in this study facilitates the simultaneous acquisition of low-and high-energy data at the same spatial and temporal position (27), which provides perfectly aligned data with significantly reduced measurement error, with no a priori decision needed for the mode of acquisition (27).…”
Section: Discussionmentioning
confidence: 99%
“…Increased angiogenesis is accompanied by an increased distribution of contrast agents in the intravascular/extravascular compartment (8), thereby resulting in a higher AEF value during the same circulatory phase. Additionally, unlike NIC and λ HU , the AEF can distinguish the relationship between different phases of the same blood circulation (26). Secondly, the spectral detector CT used in this study facilitates the simultaneous acquisition of low-and high-energy data at the same spatial and temporal position (27), which provides perfectly aligned data with significantly reduced measurement error, with no a priori decision needed for the mode of acquisition (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown quantitative color mapping of the AEF, the ratio of CT value between the AP and the portal venous phase, could increase the diagnostic performance of hepatocellular carcinoma [ 34 ]. However, few studies have investigated the clinical value of AEF or NAEF, defined as the ratio of IC or NIC in the arteriovenous phase.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, abnormal blood perfusion of portal vein and portal artery occurs. [19][20][21] It has been pointed out by some studies that significant differences were observed between hAEF of cirrhosis of different severity and that of normal control group 22,23 , suggesting that the severity of patients' condition may be determined by testing hAEF. In this study, hAEF and H/S values of patients with different Child-Pugh grades were analyzed, and the results showed that the AUC of hAEF and H/S values in evaluating the degree of liver function impairment of patients were 0.716 and 0.770, respectively, indicating that hAEF and H/S values are valuable in evaluating the degree of liver function impairment of patients with hepatitis B cirrhosis.…”
Section: Discussionmentioning
confidence: 99%